Centrality dependence of the charged-particle multiplicity density at midrapidity in Pb-Pb collisions at √sNN=2.76 TeV - Aamodt, Kenneth; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Lohner, Daniel; Lu, Xianguo; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; et al. (Physical review letters, 2011)
The centrality dependence of the charged-particle multiplicity density at midrapidity in Pb-Pb collisions at √sNN=2.76 TeV is presented. The charged-particle density normalized per participating nucleon pair increases by about a factor of 2 from peripheral (70%-80%) to central (0%-5%) collisions. The centrality dependence is found to be similar to that observed at lower collision energies. The data are compared with models based on different mechanisms for particle production in nuclear collisions.
*ALICE Collaboration: K. Aamodt, V. Anguelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, D. Lohner, X.G. Lu, J. Mercado Perez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, S. Vallero, B. Windelband [und 901 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Gesehen am 22.02.2022